Simulation of the flow through automatic valves of hermetic compressors by the immersed boundary method approach - Rodrigues, T. T.; Gasche, J. L. (My University, 2011)
The main goal of the present work is to verify the applicability of the Immersed Boundary Method together with the Virtual Physical Model to solve the flow through automatic valves of hermetic compressors. The valve was simplified to a two-dimensional radial diffuser, with diameter ratio of D/d = 1.5, and simulated for a one cycle of opening and closing process with a imposed velocity of 3.0 cm/s for the reed, dimensionless gap between disks in the range of 0.07 < s/d < 0.10, and inlet Reynolds number equal to 1500. The good results obtained showed that the methodology has great potential as project tool for this type of valve systems. © The Authors, 2011.
Keywords: Diameter ratio; Flowthrough; Hermetic compressors; Immersed boundary methods; Physical model; Project tools; Radial diffuser; Valve systems; Reynolds number; Hermetic devices